Relationship between the presence of liver metastases with histological grading, depth of invasion and nodal involvement in sporadic adenocarcinoma of the large intestine - Cambruzzi,Eduardo (2015)
ABSTRACTIntroduction:Large intestine adenocarcinoma (LIA) is the most common cancer of the gastrointestinal tract, and corresponds to the fifth most common malignancy in Brazil. The main prognostic factors related to LIA are depth of tumor invasion and perivisceral lymph nodes status.Objective:To estimate the relationship between pathological findings and the presence of liver metastases (LM) in LIA cases.Method:We evaluated 51 cases of LIA, previously submitted to surgical resection, in order to determine the following variables: topography, tumor size, macroscopic appearance, degree of differentiation, depth of invasion, nodal status, and presence of LM.Results:The average age was 64.8 years, with predominance of men (n = 26/51.0%) and lesions in the sigmoid colon (n = 18/35.3%). The main general characteristics of the sample were ulcerative-vegetative lesions (n = 20/39.2%), no annular tumors (n = 3/64.7%), moderately differentiated tumor (n = 44/86.3%), absence of mucinous areas (n = 40/78.4%), and mesocolon invasion (n = 29/56.9%). LM were found in 14 cases (27.5%), and is associated with presence of nodal metastases (p = 0.005). Tumor size (p = 0.72), macroscopic appearance (p = 0.362), histological grade (p = 0.147), and depth of invasion (p = 0.195) showed no association with LM presence.Conclusion:LIA has a wide anatomical and pathological heterogeneity. In this study, the presence of LM associated with LIA was related to perivisceral lymph nodes status, with no relation to tumor size, degree of differentiation, and depth of invasion, which suggests that identifying neoplastic angiolymphatic invasion is a possible predictor of liver involvement.